Pengetahuan, Persepsi, dan Adaptasi Petani Padi Sawah terhadap Perubahan Iklim di Kota Kendari - Farah Amirat; Haji Saediman; Sarinah Sarinah (Universitas Halu Oleo, 2021)
This study aims to determine the knowledge, perceptions, and adaptation of lowland rice farmers to climate change in Kendari City and to analyze the factors that influence farmers to adapt. The study population was 224 lowland rice farmers in Kendari City. Sampling was done by using non probability sampling method with purposive sampling. The number of samples is 69 farmers. The variables in this study include: farmers 'knowledge, farmers' perceptions of indicators of climate change, and factors that influence farmers in adapting to climate change. Correlation test is used to determine the factors that have a significant relationship value to the farmers' decision to adapt, and is followed by logistic regression tests. The study results show that only a small proportion (20.29 percent) of farmers understand the phenomenon of climate change. Farmers who have local knowledge in reading climate are 21.74 percent. Farmers' perceptions of climate change indicators include hesitating on rising air temperatures, agreeing to unpredictable rainy and dry seasons and doubting the increase in extreme weather events. Farmers' perceptions of the impacts of climate change include agreeing that floods and droughts occur more frequently, crop failure / puso increases, attacks by pests and diseases increase, and production decreases. Factors that influence farmers' decisions in adapting are: period of farming experience, education, training and frequent receiving of agricultural information.Keywords: knowledge; local knowledge; perceptions; adaptation; climate change.